Poor air quality as an important predictor of climate change in Delhi - YADAV, GAURAV; SINGH, GEETA; ATTRI, S.D. (MAUSAM, 2023)
The continuous change in climatic conditions has created a very difficult situation for the people living all over the world. The cities with higher population and poor air quality have been hard hit by the rising temperature and humidity, bad air quality of an urban environment plays a significant role in affecting climatic variables. As Delhi, the capital of India, tops the list of air pollution hotspots among all top polluted cities around the world is selected for this study. Through this study a relationship was assessed, among criteria air pollutants and meteorological parameters. It was hypothesized that criteria air pollutants will positively predict the change in temperature and relative humidity (pillars of climate change) during daily dataset(January 01, 2015 – December 31, 2021) and average annual dataset (2000 to 2021) in Delhi. To test this hypothesis, elastic net-applied regularization has been used in model exploration and coefficient estimation using EVIEWS 12. It was found that during the selected study period, most of the criteria air pollutants were playing a significant role in increasing the changes in climatic conditions of Delhi. This research further explains about the interlinkage between air pollution and climate change with the help of available literature.